2018
DOI: 10.1021/acs.langmuir.8b01914
|View full text |Cite
|
Sign up to set email alerts
|

Saturn-Shaped Ice Burst Pattern and Fast Basal Binding of an Ice-Binding Protein from an Antarctic Bacterial Consortium

Abstract: Ice-binding proteins (IBPs) bind to ice crystals and control their growth, enabling host organisms to adapt to subzero temperatures. By binding to ice, IBPs can affect the shape and recrystallization of ice crystals. The shapes of ice crystals produced by IBPs vary and are partially due to which ice planes the IBPs are bound to. Previously, we have described a bacterial IBP found in the metagenome of the symbionts of Euplotes focardii ( EfcIBP). EfcIBP shows remarkable ice recrystallization inhibition activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…Basal plane binding is a requirement for hyperactivity, but some IBPs with weak TH activity, like the Lp IBP from grass, also bind the basal plane . Indeed, FIPA analysis of Tis IBP6 and Euplotes focardii bacterial consortium IBP ( Efc IBP) showed that these moderate IBPs are able to bind basal and other planes . This binding pattern to ice crystal planes was confirmed also for the moderate IBP isoform 11 from the sea‐ice diatom Fragilariopsis cylindrus ( fc IBP11) by laser confocal fluorescence microscopy of a single ice crystal in a solution of the fluorescently labelled protein .…”
Section: Activity Of Duf3494 Ibpsmentioning
confidence: 69%
See 3 more Smart Citations
“…Basal plane binding is a requirement for hyperactivity, but some IBPs with weak TH activity, like the Lp IBP from grass, also bind the basal plane . Indeed, FIPA analysis of Tis IBP6 and Euplotes focardii bacterial consortium IBP ( Efc IBP) showed that these moderate IBPs are able to bind basal and other planes . This binding pattern to ice crystal planes was confirmed also for the moderate IBP isoform 11 from the sea‐ice diatom Fragilariopsis cylindrus ( fc IBP11) by laser confocal fluorescence microscopy of a single ice crystal in a solution of the fluorescently labelled protein .…”
Section: Activity Of Duf3494 Ibpsmentioning
confidence: 69%
“…Experiments on ice‐binding kinetics might help to understand the differences between hyperactive and moderate basal‐binder IBPs. Kinetics experiments carried out on the moderately active Efc IBP indicate it binds ice crystals very fast when compared to the hyperactive sbwAFP from spruce budworm .…”
Section: Activity Of Duf3494 Ibpsmentioning
confidence: 97%
See 2 more Smart Citations
“…Yet, the physico-chemical principles of the interaction between AF(G)Ps and ice remain elusive, as both experimental and theoretical studies of protein binding to ice are challenging. In recent years, computational studies [29,33,34,35,36,37] and microscopy experiments [38,39,40] have been particularly illuminating in this area. The simulations of Midya, and Bandyopadhyay [41] beautifully illustrate how AF(G)Ps can arrest growth via the Kelvin effect as originally proposed by Knight and DeVries [42,43].…”
Section: Ice-binding and Activitymentioning
confidence: 99%